Resultant muscle torque and electromyographic activity during high intensity elastic resistance and free weight exercises - Aboodarda, S.J.; Hamid, M.S.A.; Che Muhamed, A.M.; Ibrahim, F.; Thompson, M. (2013)
The purpose of this study was to quantify and compare Resultant Muscle Torque (RMT) and muscle activation (EMG) pattern, during resistance exercise comprising eight repetitions maximum (8 RM) biceps curl with elastic resistance and free weight exercise. Sixteen male and female recreationally active subjects completed 8 RM biceps curl by each of three modalities of resistance exercise: (i) dumbbell (DB), (ii) elastic tubing with original un-stretched length at the commencement of contraction (E0), and (iii) elastic tubing with 30 decrement of original length (E30) at the commencement of contraction. The magnitude of muscle activation, external force, acceleration as well as range of motion (ROM) were quantified and synchronised by specific software. The data were collected from all eight repetitions but the first (initial), the fifth (middle) and the eighth (last) repetitions were selected for further data analysis. Each selected repetition was partitioned into a concentric and eccentric phase and then each phase was further divided into three equal segments (3 concentric and 3 eccentric = 6 segments per repetition). The EMG and RMT data demonstrated a bell-shaped muscle activation and muscle torque production pattern for the three modes of exercise. The E30 resulted in 15.40 and 14.89 higher total EMG (Î¼V) as well as 36.85 and 17.71 higher RMT (N Â· m) than E0 and DB, respectively (all P <0.05). These findings support the contention that an elastic resistance device (E30) has the capacity to provide an appropriate high resistance stimulus to meet the training requirement of elite athletes. Â© 2013 Copyright European College of Sport Science.